2016
DOI: 10.1002/jbmr.2807
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte Apoptosis Caused by Hindlimb Unloading is Required to Trigger Osteocyte RANKL Production and Subsequent Resorption of Cortical and Trabecular Bone in Mice Femurs

Abstract: Osteocyte apoptosis is essential to activate bone remodeling in response to fatigue microdamage and estrogen withdrawal, such that apoptosis inhibition in vivo prevents the onset of osteoclastic resorption. Osteocyte apoptosis has also been spatially linked to bone resorption owing to disuse, but whether apoptosis plays a similar controlling role is unclear. We, therefore, 1) evaluated the spatial and temporal effects of disuse from hindlimb unloading (HLU) on osteocyte apoptosis, receptor activator of NF-κB l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
131
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 66 publications
7
131
2
1
Order By: Relevance
“…The tail-suspended animal model has been widely accepted as an effective disuse osteoporosis model for simulating bone loss [15,22,41]. In the current tail suspension experiment, bone formation was mildly inhibited and bone resorption was markedly increased in unloaded mice, these 20 changes are in accord with previous study [14,[42][43][44]. Our correlation analysis and linear regression showed that the expression level of p-eIF2α was positively associated with the number of bone-forming osteoblasts, and negatively associated with that of bone-resorbing osteoclasts.…”
Section: Discussionsupporting
confidence: 86%
“…The tail-suspended animal model has been widely accepted as an effective disuse osteoporosis model for simulating bone loss [15,22,41]. In the current tail suspension experiment, bone formation was mildly inhibited and bone resorption was markedly increased in unloaded mice, these 20 changes are in accord with previous study [14,[42][43][44]. Our correlation analysis and linear regression showed that the expression level of p-eIF2α was positively associated with the number of bone-forming osteoblasts, and negatively associated with that of bone-resorbing osteoclasts.…”
Section: Discussionsupporting
confidence: 86%
“…Blocking osteocyte apoptosis using an apoptosis inhibitor has been shown to prevent bone loss induced by hindlimb unloading (Cabahug-Zuckerman et al, 2016). As BAIBA production is increased with exercise (Roberts et al, 2014), the hindlimb unloading assay, a model for disuse or lack of exercise, was performed to determine if BAIBA could prevent bone loss.…”
Section: Resultsmentioning
confidence: 99%
“…The detrimental effects of unloading on bone mass through osteocytes are well described (Basso and Heersche, 2006), and it has previously been shown that blocking osteocyte apoptosis prevents bone loss due to hindlimb unloading (Cabahug-Zuckerman et al, 2016). We found that providing L-BAIBA in drinking water for 2 weeks of hindlimb unloading retained bone mass, more so in males than females, most likely due to the greater amount of trabecular bone in males compared to females even with using 3-month-old females as compared to 5-month-old males.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this different appetite and resorption behavior is that dentin contains more matrix proteins of noncollagenous origin, such as osteopontin, when compared with bone (Azari et al 2011). The absence of regulatory osteocytes and osteocyte proteins in dentin may also account for the quantitative differences (Cabahug-Zuckerman et al 2016). Pretreatment with osteopontin or dentin sialoprotein has been reported to induce an increase in IL-1 (Yao et al 2008).…”
Section: Clastic Cell Adhesion: Integrins and Extracellular Matrix Prmentioning
confidence: 99%